Circumstantial social entrepreneurship: Exploring inclusive, social innovation in the transition from shadow to mainstream economic spaces. A case study of informal sector recycling activities in Bulawayo, Zimbabwe - Ndlovu, Sinqobile Sichelesile (Graduate School of Business (GSB), 2018)
As global solid waste management systems evolve to include wider elements of sustainability, developing countries are struggling with how best to work with a growing informal sector. This research seeks to investigate how developing country mainstream solid waste management systems can harness the opportunities presented through the informal recycling sector. This research explores the dialogue around „formalisation of the informal‟ and „integration of informal recycling sector into mainstream solid waste management systems‟, approaching this from an informal sector perspective. The research endeavours to offer insights to this discourse from an inclusive, social innovation approach. The research looks at what business models the informal recycling sector use as they adopt or adapt industrialised practices and how these harness inclusion and social innovation. The research area is Bulawayo, Zimbabwe with the informal recycling sector as case study. The main research question is “How can we harness inclusion and social innovation as the informal sector transitions into mainstream economic spaces?” The research employs an inductive qualitative approach through a rapid ethnography, focus group discussions and semi-structured key informant interviews. Key concepts explored in this research include „circumstantial social entrepreneurship‟, „generational informality‟, „value chain alliances‟, „public, private, community and informal sector partnerships (PPCIPs)‟ and „inclusive development as a pre-requisite to formalisation‟. By unpacking the business models employed by the informal recycling sector and how inclusive, social innovation opportunities inherent in these can be harnessed during the transition from shadow to mainstream economy spaces, this research intends to offer progressive approaches on how to unlock shared value during the graduation of the informal recycling sector from shadow to mainstream socio-economic spaces. Additionally, the outputs of this research aim to contribute to context-specific knowledge on types of non traditional social entrepreneurial activity within informal spaces and how these push boundaries of inclusive, social innovation.